Kelayakan Pengembangan Usaha Gula Semut CV Agroberdikari Di Kecamatan Sempor, Kabupaten Kebumen - Sarah Hanifa; Nia Rosiana (Forum Agribisnis, 2020)
Crystal sugar has a high potency to develop because of the growing demand for crystal sugar on a local and international scale. CV Agroberdikari is a company that produces crystal sugar in Kebumen District. The company needs investment to develop a development that increases the production of crystal sugar. Feasibility analysis needs to be done to see whether or not the business is executed when the company is developing based on non-financial aspects and financial aspects. Aspects assessed on non-financial aspects are market aspects, technical aspects, management and legal aspects, social and economic aspects, and environmental aspects. Assessment on financial aspects based on investment criteria of NPV, Net B/C, IRR and Payback Period and sensitivity analysis. Analysis results of non-financial aspects that the business is declared worthy to run. Analysis of financial aspects under normal conditions resulted in NPV Rp 708.012.338, Net B/C 2,64, IRR 29 per cent and PP 5,7 years. In development, conditions produce NPV Rp 1.003.257.059, Net B/C 3,74, IRR 45 per cent, and PP 4,9 year. The results of financial analysis can be stated that business development is worthy to run. The results of sensitivity analytic showed that the price increase of raw materials was more sensitive than the decrease in sugar production. Companies need to increase the number of suppliers of raw materials and add investment goods to increase consumer demand can be fulfilled and anticipate the increase of raw material prices.